Creating networks in chemistry : the founding and early history of chemical societies in Europe - Nielsen, Anita Kildebæk; Štrbáňová, Soňa (Special publication (Royal Society of Chemistry (Great Britain)) ;, 2008)
The book focuses on the chemical societies established all over Europe and the process and further development of the these societies before World War I, and in exceptional cases up to 1930.